2021
DOI: 10.1001/jamanetworkopen.2021.11858
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Comprehensive Care for Joint Replacement Model With Disparities in the Use of Total Hip and Total Knee Replacement

Abstract: This cohort study evaluates whether the implementation of a large-scale Medicare policy is associated with unequal use of and access to joint replacement care among older adults from various racial/ethnic groups and socioeconomic backgrounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 43 publications
1
42
0
Order By: Relevance
“…These findings have implications for payment reform under the Comprehensive for Joint Replacement model, Medicare’s mandatory bundled payment model. 13 , 34 Current incentives, focusing on outcomes, without addressing patient risk factors emerging from area deprivation would only serve to further enhance provider motivation to select patients with lower risk for negative outcomes based on geographic residence. This will only serve to exacerbate disparities in access to care for patients from neighborhoods associated with lower socioeconomic means.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have implications for payment reform under the Comprehensive for Joint Replacement model, Medicare’s mandatory bundled payment model. 13 , 34 Current incentives, focusing on outcomes, without addressing patient risk factors emerging from area deprivation would only serve to further enhance provider motivation to select patients with lower risk for negative outcomes based on geographic residence. This will only serve to exacerbate disparities in access to care for patients from neighborhoods associated with lower socioeconomic means.…”
Section: Discussionmentioning
confidence: 99%
“…By failing to take into account the disparities associated with TJA surgical outcomes, we run the risk of penalizing institutions that provide care to the economically vulnerable and underserved patients who underwent TJA, thus encouraging discrimination against these populations. 10 , 11 , 12 , 13 Exploring the role of these factors and relationships between them would advance the understanding on how social factors become “embodied” in the risk for postsurgery outcomes and enable considerations for appropriate interventions and payment policy adjustments. 14…”
mentioning
confidence: 99%
“…In our study, using dual eligible insurance status as a surrogate for lower socioeconomic status, patients with dual eligible insurance were less likely to be white and married, and more likely to be current tobacco smokers. Thirukumaran et al [20] found recently increasing healthcare disparities under the CJR, showing non-hispanic white non-dual eligible Medicare beneficiaries saw an increased TKA usage, while black dual eligible beneficiaries saw a decreased TKA usage.…”
Section: Discussionmentioning
confidence: 99%
“…Using the original randomization scheme to identify CJR hospitals in a sensitivity analysis, we found that this sensitivity analysis did not change our conclusion regarding the decrease in racial differences in readmissions. Another concern is highlighted by the finding, reported by Thirukumaran et al, of increased racial differences after CJR implementation in the odds of receiving a total knee arthroplasty 25 . We did not find evidence of post-CJR patient selection in our data, as we saw no trends in racial differences in terms of patient age, sex, and comorbidity burden (Figs.…”
Section: Discussionmentioning
confidence: 99%